Strategi Pengembangan Lembaga Keuangan Mikro Syariah (Studi Kasus pada BMT Tawfin Jakarta) - Ahmad Sapudin; Mukhamad Najib; Setiadi Djohar (Department of Islamic Economics, IPB University, 2017)
This research was conducted to analysis the development strategy of Islamic microfinance institutions at BMT Tawfin, Jakarta. The aims of this research were 1) identifying health performance of BMT Tawfin based on health assessment model from Ministry of Cooperatives and Small and Medium Enterprises 2) identifying internal and external strategic factors that may influence BMT Tawfin in business development, 3) arrange appropriate formulation and alternative strategy for development of BMT Tawfin in microfinance bussines. Primary data and secondary data were gathered at this research. The research was also conducted using several analytical methods such as health assessment analysis, internal factor evaluation (IFE) and external factor evaluation (EFE) matrix, internal-external(IE) matrix, SWOT and blue ocean strategy (BOS). Based on the health assessment performance analysis, BMT Tawfin obtained score of 51,70 which was in under supervisory criteria. According to the IFE and EFE matrix results, the differences of each weighted values were 2,497 and 2,010 respectively, so the position of the BMT Tawfin in the IE matrix was situated at quadrant V. Therefore BMT Tawfin needs to use a hold and maintain strategy. Based on SWOT matrix result, priority strategies that can be implemented by BMT Tawfin was weakness – oportunities (WO) strategy. The BOS sequenced the new proposed 5 strategy priority. The result of the research showed new proposed strategy has eligibility as the blue ocean strategy (BOS).